2020
DOI: 10.1108/ijilt-04-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on the correlation between teacher efficacy and ICT infrastructure

Abstract: PurposeSelf-efficacy is one's belief in one's ability. In this context, information and communication technology (ICT) self-efficacy is the judgment of one's capability to use ICT – the familiar and effective teaching tools for the 21st century classrooms. The purpose of this empirical study was to investigate the correlation between teachers' ICT self-efficacy and perceived ICT infrastructure in school.Design/methodology/approachThe study employed a descriptive survey method within ex post facto research desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Online learning primarily uses the internet to deliver instruction and content of education (Watson et al, 2004 ), and virtual school is an educational organization that uses web-based methods or the internet to offer K-12 courses (Clark, 2001 ). Kundu, Bej, & Dey ( 2020b ) pointed out that access to the internet now guarantees access to universal education at the lowest cost, if not for free and is potent in bringing greater student engagement and achievement as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online learning primarily uses the internet to deliver instruction and content of education (Watson et al, 2004 ), and virtual school is an educational organization that uses web-based methods or the internet to offer K-12 courses (Clark, 2001 ). Kundu, Bej, & Dey ( 2020b ) pointed out that access to the internet now guarantees access to universal education at the lowest cost, if not for free and is potent in bringing greater student engagement and achievement as well.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, online teaching requires some skills to support a teacher’s role as an intersection point for technology, pedagogy, and content (Kundu, 2018a , b ; Russell, 2004 ; Savery, 2005 ). To provide quality online learning opportunities to students, the primary responsibility of the teacher is to select and coordinate the technology, pedagogy, and content (Koehler & Mishra, 2009 ; Kurtz et al, 2004 ; Olson & Wisher, 2002 ; Kundu, Bej, & Dey, 2020b ). Adopting new online teaching strategies linked to technology, pedagogy, and instructional plan may require teachers to undergo some key changes and move away from what they have experienced during offline teaching (Lee & Hirumi, 2004 ; O’Neil, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cultural differences have also been identified in the study of Kundu (2018c) where Indian teachers found perceiving themselves more of an authority role compared to Western teachers that negatively impact on the teachers' use of educational technology. Kundu, Bej, & Dey (2020), Vanderlinde & van Braak (2010), and Moses, Bakar, Mahmud & Wong (2016) found good ICT infrastructure yields good integration in pedagogy. Frost & Sullivan (2006) have characterized technical support as the access, operation, and troubleshooting of hardware, software, and network resources.…”
Section: Infrastructure An External Factor For Ict Integrationmentioning
confidence: 99%
“…The highest performance is observed if the teacher brings together technological, pedagogical, and integration efficiencies in its three domains [52]. In this regard, the success of ICT in education depends a lot on the digital autonomy acquired by teachers because of their digital competence, professional development, and the training provided to teachers [53].…”
Section: Use Of Ictmentioning
confidence: 99%